INTERNET OF THINGS SECURITY BASED ON BLOCKCHAIN TECHNOLOGY - Seidullayev , Madiyar (Innovative Development in Educational Activities, 2023)
Blockchain, a distributed tabulation system, rose to fame as the foundation of the Bitcoin currency. In terms of exploration and operationally successful businesses, it has experienced tremendous expansion throughout the years. Blockchain technology, which is decentralized and uses encryption as its foundation, can elegantly solve the difficult Generals Problem. For applications that require decentralized agreements among untrusted peers without the use of a centralized authority, it is therefore a solid option. The Internet of effects, a technical paradigm in which various little biases, such as detectors, actual bluffs, and RFID tags, are connected by a common dispatching medium, makes it possible for a whole new range of activities and operations.